1055 Trauma Associated Sleep Disorder Revisited. (12th April 2019) - Gordon, Nathaniel; Rizzo, Meagan; Robertson, Brian; Collen, Jacob
Abstract: INTRODUCTION: Trauma associated sleep disorder (TSD) is a unique parasomnia characterized by nightmares, disruptive nocturnal behaviors (DNB), dream enacting behavior and PSG findings of sympathetic overdrive and REM sleep without atonia (RSWA). Underlying pathophysiology may stem from trauma coupled with sleep deprivation. Some excellent series of TSD have been published but understanding of evaluation and treatment is in its infancy. We present a case series of veterans with TSD and our treatment approach. Patients were recent combat veterans referred for dream enacting behavior. All underwent a comprehensive sleep medicine evaluation including in-laboratory level-1 video PSG at an academic sleep center. Treatments were individualized. Report of CASES: We present three cases of TSD with prior traumatic experience and DNB evaluated with comprehensive video PSG who continue to receive care at our clinic. 1. A 40-year-old male with PTSD, TBI, depression and chronic pain presented for nightly history of thrashing, combative movements during sleep. PSG was notable for mild OSA and RSWA in 69% of REM epochs. Tachycardia and tachypnea were noted. The patient significantly improved with CPAP and prazosin. 2. A 35-year-old male with history notable for hypothyroidism and multiple deployments presented with combative dream enactments resulting in injury to bedpartners. PSG was notable for mild OSA, RSWA in 8% of REM epochs and tachycardia during REM. No abnormal behaviors were present on video PSG and treatment is in progress. 3. A 37-year-old male with depression, anxiety, nightmares and prior alcohol abuse on multiple antidepressants presented for DNB following deployment to Iraq. The patient did not have OSA, but PSG captured RSWA in 13% of REM epochs and a confusional arousal. He was started on melatonin due to concerns about prior alcohol abuse and awaits follow-up. Conclusion: TSD is a disabling and underreported sleep disorder potentially representing an overlap syndrome with features of both NREM and REM parasomnias. Diagnosis requires a comprehensive evaluation with video polysomnography. As observed in all reported cases, RSWA is not consistently elevated in this population, and therefore its use in diagnostic criteria warrants further evaluation. Treatment must be individualized due to extensive heterogeneity of the population.